2021
DOI: 10.3389/fpls.2021.726797
|View full text |Cite
|
Sign up to set email alerts
|

RhWRKY33 Positively Regulates Onset of Floral Senescence by Responding to Wounding- and Ethylene-Signaling in Rose Plants

Abstract: Rose plants are one of the most important horticultural crops, whose commercial value mainly depends on long-distance transportation, and wounding and ethylene are the main factors leading to their quality decline and accelerated senescence in the process. However, underlying molecular mechanisms of crosstalk between wounding and ethylene in the regulation of flower senescence remain poorly understood. In relation to this, transcriptome analysis was performed on rose flowers subjected to various treatments, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Among those we identified, some TF genes have similarities to known genes, such as ANAC092 and WRKY40 , which are linked to senescence and autophagy in Arabidopsis [ 41 , 42 ]. In addition, senescence-related TF genes, including RhWRKY33 and RhHB6 , have been found in rose [ 8 , 18 ]. As for protein kinases, except for a few reports on the regulation of mitogen-activated protein kinases, there is not a lot of amount of data about protein kinases involved in rose plant growth and development [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those we identified, some TF genes have similarities to known genes, such as ANAC092 and WRKY40 , which are linked to senescence and autophagy in Arabidopsis [ 41 , 42 ]. In addition, senescence-related TF genes, including RhWRKY33 and RhHB6 , have been found in rose [ 8 , 18 ]. As for protein kinases, except for a few reports on the regulation of mitogen-activated protein kinases, there is not a lot of amount of data about protein kinases involved in rose plant growth and development [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that ethylene modulates flower senescence by regulating the expression of some senescence-associated genes in rose. Several transcription factors including RhHB1/6, RhMYB108, RhERF113, and RhWRKY33 were reported to regulate ethylene-induced petal senescence and the expression of RhSAG12 (the rose homolog of SAG12 ) [ 6 , 7 , 17 , 18 ]. However, the molecular mechanism of ethylene-induced flower senescence remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that some WRKY family TFs such as DcWRKY75 participate in the ethylene biosynthesis pathway to mediate and regulate carnation petal senescence (Xu et al., 2021), while the current research on WRKY33 is mainly focused on plant defense responses. A recent study showed that RhWRKY33 is involved in mediating ethylene‐induced petal senescence in rose ( Rosa hybrida ) (Jing et al., 2021). Transcriptome and RT‐qPCR analyses revealed that DcWRKY33 expression was significantly upregulated in ethylene‐treated carnation petals (Figure 1c,d).…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of the transcriptome changes during mechanical wounding could contribute to artificially inducing the production of secondary metabolites. One of the important steps in the process of repair from mechanical wounding is the reprogramming of the transcriptome, and it involves several genes including those encoding TFs such as WRKY and AP2 [8][9][10][11]. The 'repair' genes encode proteins that function in signaling, phytohormone regulation, transcription regulation, and the synthesis of secondary metabolites [8].…”
Section: Introductionmentioning
confidence: 99%